To solve the system of equations, we can use either the substitution method or the elimination method. Let's use the elimination method:
First, let's eliminate the y variable by multiplying the first equation by 2 and the second equation by 3:
(2) * (2x - 3y) = (2) * 16
4x - 6y = 32
(3) * (3x + 2y) = (3) * 11
9x + 6y = 33
Now, we can add the two new equations together:
(4x - 6y) + (9x + 6y) = 32 + 33
13x = 65
Divide both sides of the equation by 13 to isolate x:
13x/13 = 65/13
x = 5
Now that we have the value of x, we can substitute it back into one of the original equations to solve for y. Let's substitute x = 5 into the first equation:
2(5) - 3y = 16
10 - 3y = 16
Subtract 10 from both sides of the equation:
-3y = 16 - 10
-3y = 6
Now, divide both sides of the equation by -3 to isolate y:
-3y/-3 = 6/-3
y = -2
Therefore, the solution to the system of equations is x = 5 and y = -2.
2x - 3y = 16
3x + 2y = 11
solve the system of equations
1 answer